2008
DOI: 10.1002/jbm.b.31249
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo evaluation of the biocompatibility of anodic plasma chemical (APC) treatment of titanium with calcium phosphate

Abstract: Implant loosening is an unresolved complication associated with prosthetics. Previous studies report improved osseointegration with hydroxyapatite (HA) or tri-calcium phosphate coatings. Unfortunately, the brittleness and low strength of these coatings in adhesion to the implant or internal cohesion is problematic, restricting their use. Anodic plasma-chemical (APC) treatment, an advanced anodisation method, allows for porous oxide layer formation with incorporation of calcium and phosphate directly into the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
3
5
0
Order By: Relevance
“…Surface chemistry also influences the initial protein interactions with the surface, but as shown with the XPS results, the surface chemistry was not altered by the roughening processes, with a final electropolishing step neutralising any possible previous step changes [Table (B)]. The results would therefore support that surface microtopography is influencing the body's reaction immediately upon implantation through protein adsorption, cell adhesion (or not) and cell differentiation as previously published, right up to the late tissue reactions, as shown here and in other studies …”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Surface chemistry also influences the initial protein interactions with the surface, but as shown with the XPS results, the surface chemistry was not altered by the roughening processes, with a final electropolishing step neutralising any possible previous step changes [Table (B)]. The results would therefore support that surface microtopography is influencing the body's reaction immediately upon implantation through protein adsorption, cell adhesion (or not) and cell differentiation as previously published, right up to the late tissue reactions, as shown here and in other studies …”
Section: Discussionsupporting
confidence: 87%
“…The stability and integration of implants with bone also depends upon the nature of the interface . Data regarding bone contact from this study confirmed previous observations implicating a positive correlation between increased surface micro‐roughness and bone attachment (Figures and ) . In contrast to the above mentioned studies where the implants had initial direct bone contact, the present study was not originally designed for this evaluation, but for soft tissue and capsule evaluation upon the upper plate surfaces (Figures and ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In terms of hard tissue response we have shown that smoother surfaces compared to the clinically available 'standard' micro-rough counterparts hold potential for reducing bony over-growth by essentially reducing osteoblast 'specific' genotypic expression via alterations in the cell shape and cytoskeletal organization (Hayes et al, 2008). We have also observed this effect translated to a tissue level in vivo, where the importance of the surface characteristics of clinically used devices were found to directly control specific tissue outcomes (Welton, 2006;Pearce et al, 2008;Schlegel et al, 2009).…”
Section: Introductionmentioning
confidence: 76%
“…Recently Schlegel et al (2008) used anodic plasma-chemical (APC) treatment to fabricate a porous oxide layer incorporating calcium and phosphate directly in the oxide. This produced superior adhesive strength to a conventional calcium phosphate coating, offering potential for long-term osseointegration.…”
Section: Surface Functionalizationmentioning
confidence: 99%